O ensino de filosofia no Brasil: a sua formação discursiva no contexto universitário de 1930 a 1968 - Perencini, Tiago Brentam [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research meets a philosophical aspiration of seeking to respond to a problem raised in the course of my formation journey: How did the discursive formation of philosophy teaching at university level occur in Brazil? I use as a material series education and philosophy journals published between 1930 and 1968, the Brazilian university's formative years. I revise the set of files, with the general purpose of understanding the discursive formation of philosophy teaching in the period, and use Michel Foucault's archaeology as procedure. In agreement with this standard, we analyze the files suspending causal categories such as author, origin and text, a movement that causes this story to not be told by enunciating subjects or by the elaboration of their texts and contexts produced. I propose a descriptive analysis through the emergence of statements that made the formation of this speech possible and transpose the narrative of a causal story for the philosophical practice of diagnosing insurgencies as a discursive and archaeological event. In total agreement with this purpose, I cross two positivities: (1) philosophy as a theoretical strategy, from where I find two discursive continuities: (1a) philosophy related to science and (2a) philosophy related to philosophizing. From both positions, I transpose discursive practices related to philosophy teaching: (2) The teachability field as a concept, whereas I see four dispersions: (2a) teaching, (2b) studying, (2c) introduction and (2d) learning in relation to philosophy. From these, different ways of relating to philosophy teaching can be handled. After such movements, I affirmatively verify the hypothesis that philosophy teaching follows discursive practices within pedagogy and philosophy. I also contribute to the systematization of this field of knowledge's database, in the Brazilian academic debate.

Esta pesquisa cumpre uma ambição filosófica, que é a de procurar responder à problemática levantada no decorrer de meu percurso formativo: Como ocorreu a formação discursiva do ensino de filosofia em nível universitário no Brasil? Utilizo como série material os periódicos de educação e de filosofia publicados entre 1930 a 1968, anos formadores da universidade brasileira. Reviso o conjunto de arquivos, com o propósito geral de compreender a formação discursiva do ensino de filosofia no período, e sirvo-me da arqueologia de Michel Foucault como procedimento. Na concordância desse referencial, analiso os arquivos suspendendo categorias causais como autor, origem e texto, movimento que faz com que essa história não seja contada pelos sujeitos enunciadores ou pela elaboração de seus textos e contextos produzidos. Proponho uma análise descritiva pela emergência dos enunciados que possibilitaram a formação desse discurso e transponho a narrativa de uma história causal para a prática filosófica de diagnosticar insurgências como acontecimento discursivo e arqueológico. De total acordo com esse propósito, cruzo duas positividades: (1) A filosofia como estratégia teórica, de onde encontro duas continuidades discursivas: (1a) a filosofia relacionada à ciência e (2a) a filosofia relacionada ao filosofar. De ambas as posições, transponho práticas discursivas relacionadas ao ensino de filosofia: (2) O campo da ensinabilidade como conceito, ao passo que visualizo quatro dispersões: (2a) ensino, (2b) estudo, (2c) introdução e (2d) aprendizado na relação com a filosofia. Dessas se podem manusear modos diferentes de se relacionar com o ensino de filosofia. Após tais movimentos, verifico afirmativamente a hipótese de que o ensino de filosofia segue práticas discursivas no interior da pedagogia e da filosofia. Também contribuo para a sistematização da base de dados acerca desse campo de saber, no debate acadêmico...
Keywords: Filosofia - Brasil - Estudo e ensino; Ensino superior - 1930-1968; Educação - Historia; Education, Higher